1989
DOI: 10.3386/w2950
|View full text |Cite
|
Sign up to set email alerts
|

Real Exchange Rates in the Developing Countries: Concepts and Measure- ment

Abstract: This paper deals with three important issues related to real exchange rates. First, it discusses the analytical concept of real exchange rate (RER) placing particular emphasis on providing an operational definition for the equilibrium real exchange rate. Of course, once this concept is defined we can begin to discuss in a meaningful way what we mean by real exchange rate misalignment, or deviations of the actual RER from its equilibrium value. Second, this paper deals with problems associated with measuring re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 9 publications
2
45
1
3
Order By: Relevance
“…In turn, this induces the need to generate a depreciation in the real exchange rate. However, Edwards (1989b) has shown that these initial theoretical approaches were too simplistic. He has argued that a trade liberalization does not have an unambiguous effect, since there are two different effects at work, a substitution and an income effect, that operate in opposite directions.…”
Section: Trade Opennessmentioning
confidence: 99%
“…In turn, this induces the need to generate a depreciation in the real exchange rate. However, Edwards (1989b) has shown that these initial theoretical approaches were too simplistic. He has argued that a trade liberalization does not have an unambiguous effect, since there are two different effects at work, a substitution and an income effect, that operate in opposite directions.…”
Section: Trade Opennessmentioning
confidence: 99%
“…The BEER approach -in a similar fashion than Williamson's (1994) fundamental equilibrium exchange rate (FEER) approach [9], explains the real exchange rate behaviour in terms of economic fundamentals using * Internal balance means that the economy operates at the full-capacity output, while the external balance refers to the current account sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IFS (IMF) 2017. Theoretically, the influence of terms of trade on the REER cannot be signed a priori, as this depends on whether income or substitution effects dominate [8,9].…”
Section: Lreer Lbse Lopen Ltotmentioning
confidence: 99%
See 2 more Smart Citations